2011
DOI: 10.1177/030089161109700524
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic ileal neobladder reconstruction in a woman who developed squamous cell carcinoma of the urinary bladder after kidney transplantation

Abstract: The case of a 62-year-old woman who developed squamous cell carcinoma of the bladder 16 years after a kidney transplant is reported here. After the transplant, immunosuppressive therapy was maintained with cyclosporin A (200 mg/day) and the patient's serum creatinine level was 0.9 mg/dL. She was diagnosed with squamous cell carcinoma of the bladder 16 years later and underwent radical cystectomy with an orthotopic ileal neobladder. The Studer technique was used and the afferent ileal loop was anastomosed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In the literature, studies on the sarcomatoid variant in bladder cancer after kidney transplantation are rare [13,14]. Also, squamous cell bladder carcinoma has been reported in a limited number of cases after kidney transplantation [15,16]. As we know, our case is the first report in the literature to describe both sarcomatoid and squamous variants in bladder cancer after renal transplantation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the literature, studies on the sarcomatoid variant in bladder cancer after kidney transplantation are rare [13,14]. Also, squamous cell bladder carcinoma has been reported in a limited number of cases after kidney transplantation [15,16]. As we know, our case is the first report in the literature to describe both sarcomatoid and squamous variants in bladder cancer after renal transplantation.…”
Section: Discussionmentioning
confidence: 70%
“…There is no clear consensus on the type of urinary diversion in patients with renal transplant recipients. However, since orthotopic neobladder is more favorable in terms of patient comfort, orthotopic neobladder has been the preferred method in recent studies [16,17]. However, the orthotopic neobladder method may have more problems such as frequent urinary tract infections due to intermittent catheterization and the development of metabolic complications due to increased urine absorption from the intestinal urinary diversion [17].…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be only one report in the literature describing renal tuberculosis requiring nephrectomy and the subsequent development of squamous cell carcinoma of the bladder following transplantation [ 10 ]. Whether either of these patients were at a greater risk of developing squamous cell cancer of the bladder pre-transplant is unclear, but nevertheless an interesting query for meaningful investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The single cases of the orthotopic ileal neobladder reconstruction in patients with squamous cell carcinoma of the bladder have been reported. It has been shown that this procedure is safe and feasible in kidney transplant 7 .…”
Section: Discussionmentioning
confidence: 99%